The Effectiveness of the Nutrition Care Process on Improving Nutritional Status for In-Patient Department (IPD) Patients - Maneesing, Tanu-udom; Pramyothin, Pornpoj; Pitisrisit, Manussanun; Bumrungcheep, Kanicha; Kumsem, Anong; Cumnon, Piyatida; Tiya-a-monlert, Chutimon; Khasuwan, Kamonchanok; Satapornpanich, Nattiya; Jampatong, Narudon; Sirijindadirat, Nanthipha; Uttamachai, Chavit (Journal of Nutrition Association of Thailand (Online), 2021)
Malnutrition among In-Patient Department patients is common due to insufficient or inappropriate energy and protein intakes. While consultations with nutrition-specialized physicians can contribute significantly to case management, these physicians cannot act alone. A multidisciplinary team is essential to provide patients with support for adequate and successful nutritional care. Using a pre-post study design, this study examined if a Nutrition Care Process (NCP) could improve in-patient energy and protein intakes and overall nutrition based on nutrition assessment scores. Sixty-four in-patients needing nutritional consultations were recruited from January 2019 to March 2020 of which 86% were general IPD patients and 14% were palliative care patients. The NCP flow started with a nutrition-specialized physician referring patients to a dietitian using a physician’s order sheet, the Line® program, or a nurse notifying the dietitian. The dietitian then conducted dietary assessments to determine protein and energy intakes and nutritional status using either the 7-point Subjective Global Assessment for general patients or Patient-Generated Subjective Global Assessment for cancer patients. Nutritional status was monitored every 1-7 days. The dietitian prepared reports and messages that were sent to physicians via Line® and provided dietary advice specific to conditions or diseases before patient discharge. The Key Performance Indicator, which was set at >60% for each parameter, was used to evaluate improvements in energy and protein intakes and nutritional status. Results showed that after the NCP, 80% of the patients had adequate energy and protein intakes, whereas 82% had better nutritional assessment scores. The NCP, therefore, is important for improving the nutritional status of malnourished IPD patients and achieving adequate energy and protein intakes.